Fingerprint Reconstruction using AVAE Algorithm - Uma Mageswari, T; Nivetha, A; Jagajanani, S D; Aadithya, S (2024 Asian Conference on Intelligent Technologies (ACOIT), 2024)
Fingerprint recognition stands out as a crucial area of study in the forensic department. There are many challenges that persist in the fingerprint reconstruction field particularly partial and low-quality fingerprint impressions. This paper presents fingerprint reconstruction using Adversarial Variational Autoencoders. Here, we introduce an integrated model that blends the generative capabilities of Variational Autoencoders with adversarial training from Generative Adversarial Networks. This approach holds potential implications for enhancing biometric and forensic analysis with quality and completeness of fingerprint data.